2023
DOI: 10.14293/s2199-1006.1.sor-.ppzwvjh.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Language, Society, and Cultural Differences in Representation: The Strange Case of Malangese Boso Walikan

Abstract: This paper offers a critical response to fundamental theories of representation in the introductory section of Representation: Cultural Representations and Signifying Practices, a book written by Hall, Evans, and Nixon. As of January 2023, the book had won critical acclaims and was cited 13,500 times. The writers discuss how important a system of representation operates to connect language, society, and cultural differences in Malang, East Java, Indonesia. Using a specific case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There were studies that are related to this topic which discusses Basa Walikan. Using the Malangese slang language as a representational system, we possibly discover that a cultural difference may occur within the same society where most people share the same cultural values and speak the same language [2]. In this case, not all Malangese people like to speak their own unique slang language although they were born and grew up in Malang and can speak the slang language well.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There were studies that are related to this topic which discusses Basa Walikan. Using the Malangese slang language as a representational system, we possibly discover that a cultural difference may occur within the same society where most people share the same cultural values and speak the same language [2]. In this case, not all Malangese people like to speak their own unique slang language although they were born and grew up in Malang and can speak the slang language well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[1] Studied about the existence of 'Basa Walikan' as a communication symbol of Gen-Z in Malang. Another study [2] found that by using the Malangese slang language as a representational system, the researchers possibly discover that a cultural difference may occur within the same society where most people share the same cultural values and speak the same language. Masduqi et al found that 'Basa Walikan' was a slang language which has a representational system.…”
Section: Introductionmentioning
confidence: 99%
“…One of the strengths of CDA is its ability to reveal how certain minority individuals or groups are discriminated against in texts. In CDA, certain individuals or groups are discursively discriminated against when they are presented or depicted negatively using discriminatory discourse strategies (Blackledge, 2005;Fairclough and Wodak, 1997;Flowerdew, Li, &Trans, 2002;Irawan, 2017;Irawan and Adnan, 2018;Khosravinik, 2009;Masduqi, Chotib, & Subiyanto, 2023;Van Dijk, 1993b, 2002Wodak and Reisigl, 1999, 2001, 2007. The discriminatory discourse strategies, such as 'metaphor', 'scapegoating', and 'lexicalisation', are effectively used to construct prejudice, stereotypes, and other negative presentations (Flowerdew et al, 2002).…”
Section: Media Representations and Critical Discourse Analysismentioning
confidence: 99%